Feasibility assessment of shear wave elastography to rotator cuff muscle. Issue 2 (30th December 2014) - Itoigawa, Yoshiaki; Sperling, John W.; Steinmann, Scott P.; Chen, Qingshan; Song, Pengfei; Chen, Shigao; Itoi, Eiji; Hatta, Taku; An, Kai‐Nan
<x xml:space="preserve">Abstract</x> Pre‐surgical measurement of supraspinatus muscle extensibility is important for rotator cuff repair. The purpose of the present study was to explore the potential feasibility of a shear wave ultrasound elastography (SWE)‐based method, combined with B‐mode ultrasound, to measure the in vivo stiffness of the supraspinatus muscle non‐invasively and thus obtain key information about supraspinatus muscle extensibility. Our investigation comprised two steps. First, we determined the orientation of the supraspinatus muscle fibers in cadaveric shoulders without rotator cuff tear in order to optimize the ultrasound probe positions for SWE imaging. Second, we investigated the feasibility of quantifying the stiffness of the normal supraspinatus muscle by SWE in vivo. The supraspinatus muscle was divided into four anatomical regions: anterior superficial (AS), posterior superficial (PS), anterior deep (AD), and posterior deep (PD). Each region was examined by SWE. The SWE stiffnesses of AD, AS, PD, and PS were 40.0 ± 12.4, 34.0 ± 9.9, 32.7 ± 12.7, 39.1 ± 15.7 kPa, respectively. SWE combined with B‐Mode ultrasound imaging could be a feasible method for quantifying the local stiffness of the rotator cuff muscles. Clin. Anat. 28:213–218, 2015. © 2014 Wiley Periodicals, Inc.